2021
DOI: 10.3390/app112210704
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Methods to Produce Greener Metakaolin Composite Concrete

Abstract: Metakaolin is reactive and is widely used in the modern concrete industry. This study presents an integrated strength–sustainability evaluation framework, which we employed in the context of metakaolin content in concrete. First, a composite hydration model was employed to calculate reactivity of metakaolin and cement. Furthermore, a hydration-based linear equation was designed to evaluate the compressive strength development of metakaolin composite concrete. The coefficients of the strength evaluation model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Similarly, these tools quantify the GHG emissions with a focus on the product or service. Park et al [57], in their study of metakaolin composite concrete, use emission factors adapted from Long et al [58] for the calculation of CO 2 emissions, energy, and resource consumption [57,58]. Similarly, authors such as Ghalehnovi et al [59] and Shamsabadi et al [60] use a global warming index derived from Lippiatt [61], based on the GWP of each material and its weight.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…Similarly, these tools quantify the GHG emissions with a focus on the product or service. Park et al [57], in their study of metakaolin composite concrete, use emission factors adapted from Long et al [58] for the calculation of CO 2 emissions, energy, and resource consumption [57,58]. Similarly, authors such as Ghalehnovi et al [59] and Shamsabadi et al [60] use a global warming index derived from Lippiatt [61], based on the GWP of each material and its weight.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…Moreover, it was shown that MK replacement in cement could lower the normalized CO2 emissions and resource consumption [14]. MK has to go through a burning process like cement, whereas the temperature of MK production is between 700 °C-900 °C as opposed to 1450 °C in cement production.…”
Section: Metakaolinmentioning
confidence: 99%
“…Metakaolin consists mainly of SiO 2 and Al 2 O 3 and is highly reactive. The pozzolanic reactivity of waste glass and metakaolin strongly influences the kinetics of hydration reaction of the binder and the properties of the obtained specimens [24][25].…”
Section: Introductionmentioning
confidence: 99%